Solitary Angiokeratoma of Oral Mucosa: A Rare Presentation - Shilpa Kandalgaonkar; Suyog Tupsakhare; Ashok Patil; Gaurav Agrawal; Mahesh Gabhane; Shrikant Sonune (Case Reports in Dentistry)
Solitary angiokeratoma of oral mucosa is rare entity. The term Angiokeratoma is used to refer to several lesions, whose common denominator is the presence of dilated blood vessels in association with epidermal hyperplasia. Mucosal involvement, including oral cavity is occasionally found either as a component of the systemic variety, cutaneous involvement or isolated oral involvement. Clinically, the lesion is irregular, whitish to dark brown in color, with female predominance. The etiological factors include injury, trauma, or chronic irritation to the wall of a papillary dermis. Histologically, it is characterized by hyperkeratosis, acanthosis, and dilated vascular spaces with or without organizing thrombi in papillary dermis. The vascular spaces are partly or completely enclosed by elongated ret-ridges. Along with this reporting a case of solitary angiokeratoma affecting tongue in a 38-year-old male patient, along with the literature review is presented.